2016
DOI: 10.7554/elife.17686
|View full text |Cite
|
Sign up to set email alerts
|

A cellular and regulatory map of the GABAergic nervous system of C. elegans

Abstract: Neurotransmitter maps are important complements to anatomical maps and represent an invaluable resource to understand nervous system function and development. We report here a comprehensive map of neurons in the C. elegans nervous system that contain the neurotransmitter GABA, revealing twice as many GABA-positive neuron classes as previously reported. We define previously unknown glia-like cells that take up GABA, as well as 'GABA uptake neurons' which do not synthesize GABA but take it up from the extracellu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
147
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 152 publications
(160 citation statements)
references
References 97 publications
13
147
0
Order By: Relevance
“…Despite a deep understanding of anatomy [27][28][29][30][31] and theoretical studies [32][33][34], direct experimental evidence that addresses the potential existence and identity of C. elegans CPGs has been lacking. Obtaining a mechanistic understanding of the C. elegans motor rhythm has been difficult.…”
Section: Cpgs For Body Bending Reside In the C Elegans Ventral Nervementioning
confidence: 99%
“…Despite a deep understanding of anatomy [27][28][29][30][31] and theoretical studies [32][33][34], direct experimental evidence that addresses the potential existence and identity of C. elegans CPGs has been lacking. Obtaining a mechanistic understanding of the C. elegans motor rhythm has been difficult.…”
Section: Cpgs For Body Bending Reside In the C Elegans Ventral Nervementioning
confidence: 99%
“…However, it is not clear whether GABA and other microbiota-produced neuroactive molecules may exert their effect by localized or systemic activation of signaling pathways. In C. elegans, the number and type of GABA-containing cells and cells expressing GABA-uptake proteins and receptors are higher than previously thought and include nonneuronal cells [44]. Thus, although no intestinal GABAergic cells were reported, GABA could be pleiotropically sensed by a number of cells.…”
Section: Bacterial Gaba Is Neuroprotectivementioning
confidence: 89%
“…Neural circuits have also been identified that mediate detection and response to additional sensory stimuli including UV light, O 2 and CO 2 concentrations, electric fields, and more (Bretscher et al, 2011;Chang, Chronis, Karow, Marletta, & Bargmann, 2006;Gabel et al, 2007;Ward, Liu, Feng, & Xu, 2008). To supplement the connectome to add greater functionality, C. elegans researchers have gradually uncovered the identity of neurons that release specific neurotransmitters or express particular receptors; for example, neurons throughout the C. elegans nervous system have been identified for acetylcholine and GABA transmitter signaling (Gendrel, Atlas, & Hobert, 2016;Pereira et al, 2015; see http://www.openworm.org resource to visualize). Clear definitions of behavioral output, combined with anatomical wiring and synaptic communication, has allowed for proposed models of overall nervous system organization; for instance, coincident detection and/or a hub-and-spoke model (Ghosh, Nitabach, Zhang, & Harris, 2017).…”
Section: Neural Circuits and Behaviormentioning
confidence: 99%